Identification and quantification of project complexity from perspective of primary stakeholders in US construction projects - Kermanshachi, Sharareh; Safapour, Elnaz (Journal of Civil Engineering and Management, 2019)
Construction experts believe that complexity could adversely affect construction projects’ performance. Several studies have been focused on identifying leading complexity indicators; however, the complexity indicators from the perspective of primary stakeholders (owners, contractors, and consultants) have been rarely studied. Therefore, the aim of this study is to utilize the systematic Delphi method to identify, rank and weight the complexity indicators based on the primary stakeholders’ perspectives associated with US construction projects. Additionally, the shared entity-based complexity indicators (ECIs), as well as the weighting of entity-based complexity categories were determined and analyzed. Therefore, 101 potential ECIs were identified through a comprehensive literature review. Then, thirteen senior subject matter experts (SMEs), and three academic advisors were selected and invited to participate in a workshop to determine significant ECIs and then rank and weight them. The results reveal that the ECIs associated with complexity categories “scope definition” and “project resources” received the highest aggregated complexity weights in the aspect of the primary stakeholders. Although this study has been conducted based on US construction projects, the results would provide helpful guidance for international construction projects. Moreover, this study would assist the primary stakeholders in allocating resources properly in order to manage project complexity worldwide.